BEARING RESISTANCE OF CFRP WRAPPED CONCRETE - ABDULLAH, JASIM ALI; AWAD, SALEM YUSUF; SALIH, ODAY ASAL (Journal of Duhok University, 2021)
This research investigates the localized loading resistance of concrete specimens wrapped using Carbon Fiber Reinforced Polymers (CFRP) to indicate the enhancement of load carrying capacity and ductility of adopted specimens. A series of concentrically localized loading tests have been performed to evaluate the behavior of concrete specimens (cylinders and cubes) confined by CFRP, especially the bearing strength. The strength of concrete (normal NS and high strength HS), the loading area and the length of the wrapping were used as parameters in this study. The failure modes and experimental results of confined concrete specimens were analyzed to show the parameters effect. The results proof that the confined specimens provide a higher bearing strength, as well as, the failure modes reveal that the full wrapping length of specimens is not required and the CFRP wrapping improve the ductility of the confined specimens while the length of the wrapping is ineffective especially with specimens loaded using small bearing area.